The potentials of forest insects as alternative food - Yeni Nuraeni; Illa Anggraeni (Jurnal GALAM, 2020)
Insects have an important role for human life, both negative and detrimental roles as well as positive or beneficial roles. The role of harmful insects is as pest, while the beneficial role can be used as an alternative food source. In some areas in Indonesia, insects are also consumed as food, unfortunately there are still many people who consider insects not suitable for consumption, making the potential possessed by insects not fully utilized. This paper aims to provide information on the types of insects that can be a source of food, as well as the nutritional value contained in insects. Commonly consumed insects are termites, teak caterpillars, sago caterpillars, grasshoppers, and crickets. The insects contain high enough of nutrition that is expected to be used as alternative food source to meet community nutritional needs